Moisture supply of the sown winter common and durum wheat - G. V. Ovsyannikova; A. S. Popov; А. А. Sukharev; I. K. Kopman; Yu. V. Manukyan (Зерновое хозяйство России, 2023)
The current study was carried out in the southern part of the Rostov region in the FSBSI “ARC “Donskoy” in 2019–2022. The purpose of the study was to determine the moisture content of the winter common and durum wheat sown after various forecrops. There has been found that during the study, precipitation fell unevenly over the seasons. The amount of useful precipitation during the vegetation period of winter wheat (mean for three years) was 319.80 mm. There has been established that when sown in weedfree fallow, the total moisture consumption both over the years (278.90–445.00 mm) and on average over three years (381.40 mm) exceeded the amount of useful precipitation. On the formation of grain yield winter wheat has spent, in addition to precipitation, the productive moisture accumulated from the soil. There has been found that when sown after non-fallow forecrops, in the absence of reserves of productive moisture in the soil, the productivity formation proceeded mainly due to precipitation. When sowing winter wheat, the total moisture consumption (mean in 2019–2022) was 322.00 mm after peas and 315.50 mm after sunflower. There has been determined that the highest grain yield of the varieties ‘Zodiak’ (7.90 t/ha) and ‘Yantarina’ (6.28 t/ha) was obtained when sown in weedfree fallow, while they spent the least amount of moisture per yield unit, being 487.10 and 649, 70 m3/t respectively. When sown after sunflower, grain yield of the varieties was the lowest, and the total moisture consumption per ton of grain was the highest, being 5.60 t/ha and 599.20 m3 (the variety ‘Zodiak’); 4.02 t/ha and 869.70 m3 (the variety ‘Yantarina’). The forecrop ‘peas’ occupied an intermediate position between weedfree fallow and sunflower both in terms of productivity and total moisture consumption per ton of grain, being 6.36 t/ha and 528.60 m3 (the variety ‘Zodiak’) and 4.92 t/ha 823, 60 m3 (the variety ‘Yantarina’).